2016
DOI: 10.1080/15384101.2016.1188238
|View full text |Cite
|
Sign up to set email alerts
|

Cyc17, a meiosis-specific cyclin, is essential for anaphase initiation and chromosome segregation inTetrahymena thermophila

Abstract: Although the role of cyclins in controlling nuclear division is well established, their function in ciliate meiosis remains unknown. In ciliates, the cyclin family has undergone massive expansion which suggests that diverse cell cycle systems exist, and this warrants further investigation. A screen for cyclins in the model ciliate Tetrahymena thermophila showed that there are 34 cyclins in this organism. Only 1 cyclin, Cyc17, contains the complete cyclin core and is specifically expressed during meiosis. Delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 55 publications
4
18
0
Order By: Relevance
“…Tetrahymena thermophila cells lacking Cyc2 and Cyc17 are arrested at early crescent (∼2–3.5 h postmixing) and diakinesis-like metaphase I (∼5 h postmeiotic induction) stages of meiosis, respectively (Xu et al. 2016; Yan et al. 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Tetrahymena thermophila cells lacking Cyc2 and Cyc17 are arrested at early crescent (∼2–3.5 h postmixing) and diakinesis-like metaphase I (∼5 h postmeiotic induction) stages of meiosis, respectively (Xu et al. 2016; Yan et al. 2016).…”
Section: Discussionmentioning
confidence: 99%
“…showed that T. thermophila has a total of 34 cyclins (Yan et al, 2016b), and only four standard CDKs with exact PSTAIRE-like cyclin-binding motifs (Yan et al, 2016a). Because of the divergence between the number of annotated cyclin and CDK genes in this organism, we searched for additional CDK family members and identified a total of 20 CDKs or CDK-like genes in the T. thermophila macronuclear genome (Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…We previously identified other important meiotic regulators in T. thermophila, including the Cyc2 and Cyc17 cyclin and the Tcdk3 cyclin-dependent kinase [27,28]. To investigate the function of E2fl1/Dpl2 complex during meiosis regulation, we tracked the expression of meiotic genes in dpl2D and e2fl1D cells (Figure 3(A)) and used these data to construct a meiotic regulatory network (Figure 3(B)).…”
Section: T Thermophila Dpl2 and E2fl1 Form A Transcription Factor Comentioning
confidence: 99%
“…They regulated the expression of genes important for early prophase that functioned in DSBs formation and repair [28]. Cyc17 was essential for initiating meiotic anaphase and mainly regulated the genes involved in meiotic anaphase, including those that functioned in chromosome condensation and segregation [27]. Figure 3(A) showed a heatmap representation of the fold change in expression for these genes.…”
Section: T Thermophila Dpl2 and E2fl1 Form A Transcription Factor Comentioning
confidence: 99%